Investigation of documents of healthcare professionals who was treated in a university hospital because of alcohol/substance usage problem - Demirbaş, Hatice; Özgür İlhan, İnci and B. Doğan, Yıldırım (Journal of Dependence, 2008)
Objective: In this study, it was aimed to investigate registration ways, some demographical variables and substance use characteristics of healthcare professionals who was treated as inpatient and outpatient because of alcohol or substance use. Method: The sample consists of 77 healthcare professionals who were 87% of inpatients (n=67) and 10% of outpatients (n=10) about alcohol abuse problem as at the Ankara University Psychiatry Clinic between October 1994 and March 2007. Demographical variables, abused substances and application styles were determined by analyzing patients files. Also numbers and percentages about these variables were determined. Alcohol/substance use as a sex and working conditions were compared by the chi-square test. Results: Healthcare professionals were 6.7 % of 1004 patients who were treated as inpatients in emphasized period. Subjects were composed of 20.8 % of women (n=16) and 79.2 % of men (n=61) and they were applied about 63.6 % of alcohol, 26.0 % of only substance use and 10.4 % of alcohol with substance use problem. 47.2 % of physicians have alcohol use problem, 33.3 % have substance use problem and 19.4 % have both alcohol and substance use problem. Working in a surgical section increases the risk of using a substance other than alcohol. Healthcare professionals who are working in primary, secondary referral centers and university hospitals have higher risks of alcohol and substance use than healthcare professionals who are not working these referral centers and hospitals.(x2=7.862, sd=2, p<0.05). Most applications were made self willingly. Conclusion: Alcohol, opiates and benzodiazepines were most fenquently used substances among healthcare professionals. For this reason, prevention and treatment stages are important especially to decrease of frequency of substance use among health care professionals. Concrete steps should be more prevalent.